Civil liability for environmental damage in German and South African - Foerster, Susanne Claudia (Centre for Law and Society, 2026)
Under the heading 'Civil Liability for Environmental Damage', provisions which compensate all those who suffer environmental damage are discussed. Traditionally environmental legislation could be found mainly in administrative law dealing with resource management and conservation. Only a small proportion of those provisions dealt directly with compensation for those who had suffered pollution damage. Victims of environmental damage could usually claim damages under the general body of civil law, on the same basis as other wrongs.